2017
DOI: 10.1557/jmr.2017.137
|View full text |Cite
|
Sign up to set email alerts
|

An experimental study of influence of wire electro discharge machining parameters on surface integrity of TiNiCo shape memory alloy

Abstract: Shape memory alloys (SMAs) are unique class of smart materials with excellent physical, mechanical and biomedical properties, which have wide applications in several fields such as aerospace, robotics, biomedical, and dental etc. These alloys are well known for exhibiting shape memory effect (SME) and pseudoelasticity (PE), it is a well-established fact that they are required to be processed into functioning parts. The conventional machining affects the internal properties of shape memory alloys and hence, it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(30 citation statements)
references
References 20 publications
1
29
0
Order By: Relevance
“…In another study, Chaudhari et al [10] concluded that T on , T off , and current are the main influencing factors for the response variables of the material-removal rate(MRR), surface roughness (SR), and microhardness for the WEDMof nickel-based alloys. Soni et al [23] explored the WEDM of Ti50Ni40Co10 SMA with the output variables of MRR and SR. Increasing values of MRR and SR were reported with increasing T on , while both values decreased with increasing T off and servo voltage. Researchers used brass and copper wires as electrodes, and studied their effect on the surface integrity of amachinedSMA surface [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…In another study, Chaudhari et al [10] concluded that T on , T off , and current are the main influencing factors for the response variables of the material-removal rate(MRR), surface roughness (SR), and microhardness for the WEDMof nickel-based alloys. Soni et al [23] explored the WEDM of Ti50Ni40Co10 SMA with the output variables of MRR and SR. Increasing values of MRR and SR were reported with increasing T on , while both values decreased with increasing T off and servo voltage. Researchers used brass and copper wires as electrodes, and studied their effect on the surface integrity of amachinedSMA surface [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Alloys containing up to 10% of cobalt were also studied for material removal rate, microstructure and hardness with wire electro discharge machining technique. 29 In order for these alloys to be successfully used, the effect of cobalt on the corrosion resistance properties must be well dened. Huang et al 26 investigated the corrosion properties of these alloys in PBS solution, claiming similar behavior to cobaltless NiTi alloys and no effect of galvanic corrosion within stent.…”
Section: Introductionmentioning
confidence: 99%
“…In this research wire spark discharge machining process is adopted to perform machining study on TiNiCo smart materials by varying the elemental compassions. In WEDM process machining, performances are based on input process parameters such as pulse duration, servo voltage, wire speed and wire diameter are highly influencing parameters [10]. Removal of material from the work is based on spark erosion and vaporization which are highly controlled due to servo voltage and pulse durations [11].…”
Section: Introductionmentioning
confidence: 99%